Inflation and stabilization policies - Daniel Heymann (CEPAL Review, 1986)
Inflation, even at moderate rates, is not innocuos, since it is generally associated with erratic variations in the level and structure of prices. Nevertheless, if it is kept within certain bounds, the economy is able to find ways of adapting itself and activity can develop without undue uncertainty.